Highly Active W-H2SO4/HZSM-5 Catalyst for Direct Conversion of Methane into Aromatic - Kusmiyati Kusmiyati; N. A. S. Amin; W. A. Siswanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2007)
Dehydroaromatization of methane (DHAM) under non oxidative condition was studied over tungsten loaded HZSM-5 catalysts to produce aromatic hydrocarbons. The catalysts were prepared by impregnation method using different conditions : in neutral and acidified solution. The activity of W/HZSM-5 prepared by neutral solution and W-H2SO4/HZSM-5 prepared in acidified condition were compared. The results showed that the optimum activity of W-H2SO4/HZSM-5 catalyst exceeded that of W/HZSM-5 catalyst. The effect of Si/Al ratio of W-H2SO4/HZSM-5 catalyst was also studied. The W-H2SO4/HZSM-5 catalyst with Si/Al ratio = 0 was found to be the most promising for the DHAM reaction. The remarkable activity of the catalyst is attributed to the presence of dual effects: suitable content of octahedral polymeric and tetrahedral monomeric tungstate species accompanied by proper amount and strength of acid sites in the catalyst. © 2007 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)